Impairments of human dignity at the end of life quantitatively assessed by health care professionals: a pilot study from Germany - Derler, Florian; Mielke, Emilia Louisa L. (American journal of hospice & palliative medicine, 2024)
Background - Empirical investigations on health care professionals’ (HCPs) perception of dignity have already spotted common themes in preserving dignity in end-of-life care. However, heterogenic assessment results of varying HCP groups exist. This pilot study wants to provide further evidence on HCPs’ rating of dignity-impairing aspects based on a patient-centered concept, especially regarding different underlying job profiles and other professional characteristics. - Methods - In a quantitative study design, the rating of dignity-impairing factors in end-of-life care via an adapted version of the Patient Dignity Inventory (aPDI) was assessed. Participants of the relevant professional groups were recruited via convenience sampling from a region of Germany. - Results - From the final sample of participants, 229 questionnaires were analyzed. The overall importance of each dignity-impairing aspect in end-of-life care was considered to be very high by all different HCP groups. Nonetheless, ratings differed between professions: nursing staff had the highest ratings of importance compared to both physicians and individuals with multiple occupations. Participants with previous knowledge in bioethics also rated some aspects as more important compared to those without this feature. - Conclusion - With the findings of this investigation, an insight of how professionals rate impairments of dignity at the end of life based on a patient-centered concept is given. Thus, a link between empirical research and medical ethics is added. Potential normative implications for HCPs in practice of a dignified care can be derived, consisting of actively addressing social topics as well as further stressing ethics as a fundamental subject in the training and continuing education.
Zuerst online veröffentlicht: 7. August 2024
Gesehen am 24.03.2025